PERAN KEPALA SEKOLAH DALAM MENERAPKAN MUTU PENDIDIKAN DI SEKOLAH DASAR - Nurul Makrifah; Nur Fauzi (Jurnal Edukasi Pendidikan Guru Madrasah Ibtidaiyah, 2026)
The purpose of this study is to describe the role of the Principal at UPTD SDN Longkek 1, as well as to describe the Principal's efforts in improving the quality of education at UPTD SDN Longkek 1. Data collection techniques in this study are through observation, interviews, and documentation. While data analysis in this study uses qualitative descriptive with data reduction steps, data presentation, and conclusion drawing. The results of the study show that the Principal at UPTD SDN Longkek 1 carries out several roles including, first, the Principal as an educator, proven by improving the quality of learning, providing encouragement, and advice to teachers. Second, the Principal as a manager, this is seen from the way the Principal empowers Education Personnel through Cooperation, providing opportunities for teachers to improve their profession. Third, the Principal as an administrator by driving teacher performance improvement. Fourth, the Principal as a supervisor. Fifth, the Principal as a supervisor by compiling educational supervision programs at school; controlling teaching and learning activities, utilizing the results of supervision that has been implemented. Sixth, the Principal as a Leader. Seventh, the principal acts as a motivator, as evidenced by the physical environment, work atmosphere, discipline, encouragement, and recognition. Meanwhile, the principal's achievement in improving educational quality is evident in achievement, which is a competency measured by knowledge, success created by learning and school management, and a positive impact that significantly influences student learning outcomes.